Symposium 2: OurComixGrid: Designing a Multimodal New Media Learning Environment - Duffy, Damian; Clark, Allison N. (Proceedings of the International Conference on Networked Learning, 2008)
This paper describes the theoretical and technological underpinnings of a multimodal Web 2.0 collaborative semantic grid e-learning design environment called OurComixGrid (OCG). OCG combines new media creation and online social networking with the cyberinfrastructure of grid computing to facilitate multimodal literacy education. OCG is a multimodal Web 2.0 collaborative semantic grid e-learning environment predicated on creation and expression through sequential art, the medium of comics. “Sequential art” or the word “comics” employed as a singular noun are categorical terms used somewhat interchangeably (see, e.g. Eisner, 1985, McCloud, 1993, McCloud, 2000), to describe the medium of expression found in comic books, comic strips, graphic novels, manga (Japanese comics), webcomics (online comics), and other formats. The medium is defined by the integration of text and image and the combination of multiple images in narrative sequence. Sequential art is therefore a multimodal medium, interweaving various forms of textual and visual information in a network of symbols that combine to create the meaning of the comic. New media literacies are a necessity in our multimodal world, in which many types of information work together to form meaning. Because comics is itself a multimodal form, it has been suggested that the medium can potentially be employed as a powerful teaching tool in multimodal literacy education (Norton, 2003, Gardner, 2006, Jacobs, 2007). Comics is also a popular art form, one in which readers, and particularly young readers, feel a co-ownership of meaning within the narrative. These two aspects of comics, its multimodality and the sense of co-ownership it affords readers, are synergistic with the online participatory cultures described by Jenkins, Clinton, Purushotma, Robinson, & Weigel (2006), in which young people are increasingly using internet technology to create and share media. To capitalize on these synergies, OCG proposes an integration of the multimodal language of comics with grid computing in order to bring media creation to a virtual collaborative space for four overlapping communities: students, primary and secondary educators, art practitioners, and academic researchers. Software for art creation and organization, synchronous and asynchronous communication modules, and curriculum building applications for teachers are all features OCG will incorporate to bring these communities together, and encourage them to collaborate on innovative new media educational resources. Grid computing and open source software provides the foundation for this collaboration. The large-scale data created by OCG users will be maintained via the integrated Rule-Oriented Data System (iRODS) (http://irods.sdsc.edu) which can describe management policies and provide the ability to track how the policies are applied and their execution results. OCG also makes use of CATPAC, a self-organizing neural network application that will track user and system created tags to facilitate qualitative and quantitative study of online collaborative practices within the social network. Thus OCG is a social network that can function simultaneously as a virtual art studio, an online classroom, and a laboratory in which to study the interactions of new media and education in the digital age.